2010
DOI: 10.12693/aphyspola.117.177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Manganese Concentration on Thermoluminescent Properties of YAlO3:Mn Crystals

Abstract: This work is devoted to experimental study of the effect of manganese concentration on thermoluminescent properties of YAlO3:Mn crystals grown by the Czochralski method. A new type of emitting centers beside of Mn 4+ and Mn 2+ ions was revealed at low concentration of manganese ions in the crystal. These centers are responsible for the high-temperature thermoluminescent peak at 570 K. A potential of this thermoluminescent peak for thermoluminescence dosimetry application is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The main peaks in Figure are denoted with roman numbers. Peaks: I (activation energy 1.2 eV), II (1.4 eV), III (1.7 eV), and IV–V (2.0–2.3 eV) are present in both nonstoichiometric crystals studied and agree with previous results reported in refs , and . In the vicinity of peak II, two additional peaks, denoted as IIa and IIb (1.6 eV), can be resolved.…”
Section: Experimental Results and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The main peaks in Figure are denoted with roman numbers. Peaks: I (activation energy 1.2 eV), II (1.4 eV), III (1.7 eV), and IV–V (2.0–2.3 eV) are present in both nonstoichiometric crystals studied and agree with previous results reported in refs , and . In the vicinity of peak II, two additional peaks, denoted as IIa and IIb (1.6 eV), can be resolved.…”
Section: Experimental Results and Discussionsupporting
confidence: 90%
“…YAP:Mn 2+ single crystals were grown by the Czochralski method using the technology described in ref . Three crystals of the following nominal compositions were studied: nonstoichiometric Y 1.02 Al 0.98 O 3 :Mn­(0.02%),Si­(0.2%) (see refs and for details), nonstoichiometric Y 1.02 Al 0.98 O 3 :Mn­(0.05%),Hf­(0.2%), and stoichiometric YAlO 3 :Mn­(0.05%),Hf­(0.2%). …”
Section: Methodsmentioning
confidence: 99%
“…Further, TL studies on Sm, and Dy doped YAP crystals and Eu doped YAP nanopowders are also reported and they also exhibit multiple glow curves in the temperature range from 150 to 384 C [17,19]. Apart from single dopant, there exist a few reports on co-doping in YAP to improve the TL sensitivity [4,5,9,12,15,19]. For example, the dopant Si or Hf (which has 4+ ionic state) co-doped with Mn 2+ helps to increase the Mn 2+ /Mn 4+ ratio which eventually increases the TL emission intensity and decreases the minor glow curve intensity [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…The RE or TM dopants in YAP introduce several energy levels within the forbidden bandgap and these energy levels manifest as a characteristic optical emission or absorption under suitable external stimulation which is being effectively used as solid state lasers [3]. The optical properties of YAP crystals doped with various impurities such as Ce, Mn, Ho, Tm, Er, Pr, Cu, Dy, Sm, Yb, Cr, Eu and Nd are extensively studied [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. These doped YAP crystals also have an excellent emission characteristics in UV/visible range when irradiated with ionizing radiation and hence, it is being used in radiation dose measurements as an active element (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation